Prevalence of Dental Caries in Schoolchildren from the Galapagos Islands: ESSO-Gal Cohort Report - Ana Armas-Vega; Juan Marcos Parise-Vasco; María Cristina Díaz-Segovia; David Alejandro Arroyo-Bonilla; María José Cabrera-Dávila; María Christel Zambrano-Bonilla; Ingrid Ordonez-Romero; Andrea Caiza-Rennella; Andrea Zambrano-Mendoza; Celia Ponce-Faula; Andrés Viteri-García (International Journal of Dentistry)
Objective. Dental caries remains a prevalent disease worldwide. Several epidemiological studies have shown that it affects the oral health of the pediatric population, and the Galapagos population in Ecuador is no exception. The aim of this study was to determine the prevalence of dental caries and its association, based on baseline information from the Galapagos Oral Health Study (ESSO-Gal), in children of the Galapagos Islands, Ecuador. Methods. A cross-sectional study was conducted involving 804 children aged 2–11 years. The prevalence of dental caries was assessed using the International Caries Detection and Assessment System (ICDAS II) criteria, while the presence of dental biofilm was assessed using the Silness–Löe index. Descriptive statistics, including frequency analysis and measures of central tendency and dispersion, were performed. Inferential statistical analyses were conducted to identify associations between variables. Statistical analyses were performed using the SPSS version 25.0 statistical program. Results. The caries prevalence rates based on ICDAS II codes 1–6, 1–2, and 3–6 were 98.01%, 96.9%, and 85%, respectively. A statistically significant difference was observed among the different islands regarding the cutoff point for ICDAS II codes 3–6 (p≤0.001). Participants aged 6–11 years had the highest caries prevalence. Conclusions. The results show a high prevalence of dental caries among children in the Galapagos Islands, which increases with age. Contrary to expectations, the study did not find a significant correlation between the severity of dental caries and the presence of dental biofilm.